A Global History of the 1919 Total Solar Eclipse - Simões Ana; Luís Cristina; Soares Hugo; Gessner Samuel; Carolino Luís Miguel (HoST, 2025)
In this paper, we are looking at the British expeditions that observed the 1919 total solar eclipse in Sobral (Brazil) and Príncipe island as scientific practice embedded in their geographical, social, and world-political context. This fresh look makes steps towards a “global history” of this eclipse, and reports on contextual elements of the expeditions that have been hitherto “eclipsed” in the narratives that concentrated on the exchange of scientific arguments in a “world of ideas.” What it may mean to think of the globality of the 1919 eclipse is presented followed by an analysis of four main dimensions of this globality that include actors in context, observing totality, the eclipse lineage, and eclipse on paper.